Autoclave Technology And New Reagents For Integrated Treatment Of Russian Polymetallic Concentrates - A. V. Tarasov (The Minerals, Metals and Materials Society, 2003)
The high efficiency of autoclave processes is attributed to the fact that they are suitable for processing of refractory raw materials, have low capital costs and high productivity, ensure integrated utilization of the feed materials, produce innovative saleable products, completely eliminate any air emissions, provide low-waste or waste-less technology, as well as mechanization and automation of production processes. In the immediate future, it might be expected that autoclave processes will find use on commercial scale for production of heavy non-ferrous metals in combination with other processes (hydrometallurgical, upgrading, sorption and solvent extraction, electrolytic, etc.) to ensure: -Integrated processing of refractory ores and concentrates (pyrrhotite, zinc, copper-zinc, lead-zinc, nickel-cobalt, copper, pyrite); -Production of metallic powders of base metals as commercial products (copper, cobalt, nickel, etc.), composites on their bases, final products and saleable salts. Processing technologies incorporating autoclave processes, especially, at the stage of liberation (chemical upgrading) of minerals, are characterized generally by high overall recoveries of valuable constituents significantly exceeding recoveries common for conventional pyrometallurgical processes (for some elements by several tens of percent). An example is processing of low-grade refractory pyrrhotite concentrates using autoclave liberation of feed material under pressure of a new reagent, i.e., sulfur dioxide. The use of sulfur dioxide ensures a significant improvement in the recoveries of non-ferrous metals and platinoids to sulfide concentrate and smelting of the latter increases the capacity of the smelting units employed and minimizes the yield of discard slag and loss of metals in slag; in addition, it resolves the problem of sulfur dioxide utilization.